Breaking the Impediments to Budgetary Reforms : Evidence from Europe - Mody, Ashoka (IMF Working Papers; Working Paper ;, 2008)
Under what conditions are budget institutions likely to be strengthened? We find that fiscal deficits do not help in focusing policymakers on undertaking reforms. To the contrary, the larger the deficit, the lower is the likelihood of reforms. Large deficits apparently imply strong claims on the budget and, hence, generate unwillingness to impose self-discipline. As such, countries will tend to move either to small fiscal deficits and good institutions or large deficits and weak institutions. Economic shocks (if they are large enough) can help build a constituency for improving budget institutions. However, if forgiving markets accommodate economic shocks, even such pressure may be insufficient. Forwardlooking and credible leadership appears to be an important ingredient of the solution.